2021
DOI: 10.1590/0103-11042021e106
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences among dentistry conference speakers in Brazil

Abstract: This study aimed to evaluate possible gender differences among the invited speakers of Brazilian dentistry meetings. The selected meetings (n=15) were held in different states distributed among the five Brazilian regions. The conference programs were manually reviewed, and a database was constructed. Data analysis was performed using descriptive statistics, chi-square and Mann-Whitney tests. A total of 1,195 speakers was identified, 19.7% (n= 235) of which were women. The results of this study provide an overv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…2 Gender disparities in science, as identified in our study, are observed worldwide. Women dental scholars are also particularly underrepresented in the most prestigious roles, such as editorial board memberships, editor inchief positions (Ioannidou and Rosania, 2015)16 and being invited speakers at scientific meetings(Schroeder et al, 2013;Casadevall & Handelsman, 2014, Martorell et al, 2021). 1 7 -1 9 This is somewhat…”
mentioning
confidence: 99%
“…2 Gender disparities in science, as identified in our study, are observed worldwide. Women dental scholars are also particularly underrepresented in the most prestigious roles, such as editorial board memberships, editor inchief positions (Ioannidou and Rosania, 2015)16 and being invited speakers at scientific meetings(Schroeder et al, 2013;Casadevall & Handelsman, 2014, Martorell et al, 2021). 1 7 -1 9 This is somewhat…”
mentioning
confidence: 99%
“…Another study by Martorell et al confirms this trend in Brazil [ 31 ]. The study by Martorell showed how the imbalance was different according to the considered discipline [ 31 ]. As in our study, pediatric dentistry showed no differences between the two genders.…”
Section: Discussionmentioning
confidence: 55%
“…In the study by Martorell et al, these types of specialties are attended more by women than by men, who, instead, appear more interested in oral surgery and prosthodontic disciplines [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to remember that the feminization of Dentistry was directly linked to the trajectory of the feminist movement, which began with the struggle for more egalitarian relationships for women and later served as a motto for the development of other causes, highlighting racism and LGBTQ+ phobia and the hegemony of CIS heteronormative bodies. [33][34][35][36][37][38][39][40][41][42][43][44][45][46]…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire to assess the profile of dental school deans consisted of nine questions, including socioeconomic aspects, knowledge, affinity, and involvement with the LGBTQ+ population, as follows: 1. Age (Less than 30 years; [30][31][32][33][34][35][36][37][38][39][40] Subsequently, an attempt was made to investigate the perception of those participants regarding the LGBTQ+ population by means of two questions: 1. Degree of knowledge of who LGBTQ+ people are (Yes/completely: I know all the identities that make up the LGBTQ+ population; Yes/partially: I partially know the identities that make up the LGBTQ+ population; No/I don't know who LGBTQ+ individuals are); 2.…”
Section: Methodsmentioning
confidence: 99%